Tantangan Dan Strategi Penegakan Hukum Pajak Di Era Digital - Faris Andrawika Harahap; Niswa Auliya Lubis; Yusliani; Dini Vientiany (Jurnal Ekonomi dan Bisnis Digital, 2024)
In the rapidly growing digital era, tax law enforcement on the digital economy is becoming increasingly complex and challenging. This research discusses the challenges and strategies in efforts to optimize taxes on the digital economy. The research method used is desk research. Tax law enforcement in the digital era requires regulatory adaptation in accordance with technological developments and widespread online transactions. The main challenges include the identification of tax subjects, the imposition of Value Added Tax (VAT) on cross-border transactions, and flexibility in tax policy formulation to respond to the dynamics of the digital economy. An effective tax law enforcement strategy involves a deep understanding of the digital economy, evaluation of existing regulations, international cooperation, and investment in technology and infrastructure. With coordinated measures, the government can overcome challenges, improve tax compliance, and ensure an adaptive tax system in the digital era.